A-RADIO DAN IMPLEMENTASI KOMUNIKASI DAKWAH MELALUI PROGRAM REHAT - Nasution, Nadya Amalia; Istiani, Ade Nur; Aini, Zelin Trisna (Farabi, 2024)
A-Radio 101.1 Fm is an information medium, using its role as a da’wah medium, in the REHAT program (requests and advice) the application of da'wah communication is carried out by broadcasters in conveying da'wah messages. The decline in radio users is due to the large number of internet users, especially social media, which makes radio abandoned. Radio competition in Bandar Lampung is very tight, making radio owners need innovations that are used to maintain the existence of a radio. This study uses a qualitative descriptive approach, using the type of field research. The results of this study describe the application of da'wah communication carried out on radio programs using several stages of application, in the request and advice format using the Al-Mauidzah al-Hasanah method, through bil-lisan da'wah used by broadcasters. The innovation of da'wah broadcast content carried out by A-Radio in the REHAT program is the use of songs as da’wah material.